Broiler performance and avian uncoupling protein mRNA expression during acute heat stress as influenced by thermal manipulation and dietary fat source - Jansen van Rensburg, Christine (University of Pretoria, 2021)
Thesis (PhD (Animal Science))--University of Pretoria, 2021.